Upaya Guru PKN Dalam Mengembangkan Kualitas Moral Siswa Kelas V SDK Lamawohong Desa Lamawohong Kecamatan Solor Barat - Asmon Kewuan, Alexius Relianus; Moh. Fitri; Abdul Muis Kasim (International Forum of Researchers and Lecturers, 2024)
The aim of this research is to find out: (1) The efforts of the Civic’s teacher in developing students’ moral quality in SDK LAMAWOHONG , Rubitvillage, District, Regency and(2) The challenges encountered by the teacher in developing student’s moral quality. This research was being held on February 29rd until March 29st, 2023. The type of this research is a qualitative research and the data collecting techniques was by using observation, documentation and interview. The result of this research shows that teacher as the moral agent should integrating the moral values by using Moral education, norm, ethics and religion in their learning process, and as the motivator by giving reward and punishment to the students. The challenges of this research were a limited time allocation, peer friends association, student’s disobedience behavior, and globalization impact in culture. The conclusion of this research is the Civics teacher had given good efforts in developing students’ moral quality. It was shown in some great efforts that had been given in their learning process.